Quality Management System: An approach to efficient production (Research, Society and Development, 2023)
The Quality Management System - SGQ, brings through application means and tools, the standardization of processes that deliver, as one of the results, the added value to the customer. The company's quality implementation and conformation processes consist of medium/long term processes that must be constantly monitored and continuous improvements applied. This study aims to carry out a bibliographical survey focusing on quality management tools for efficient production with application in various industry sectors. Thus, case studies available in the bibliographies of the last 16 years are taken as a basis, as well as detailing tools in order to assist in the definition of goals and indicators for its processes, presenting to leaders the importance of implementing and/or improving the program of the quality within the enterprise, where it has positive and satisfactory results using quality management tools.